The Role of Stakeholders in Conseravation Governance in The Upstream Bedadung Watershed - Petrina, Jenitra Milan; Idah Andriyani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
The upstream of the Bedadung watershed is a catchment area. Now Bedadung watershed does not function optimally because of illegal logging and the change in function of protected forest to production forest. There was an increase in erosion, landslide, and flood. This research aims to identify conservation activities and Identify the roles of stakeholders in governance upstream Bedadung watershed. The result of the first purpose is conservation activities in the fourth Sub-watershed with exploratory, descriptive analysis: (1) Jompo Sub-watershed (coffee plants, teak plants, and terraces), cover crops, DAM controller, (2) Antrokan Sub-watershed such as durian terracing, use of organic mulch, sengon plants with elephant grass, (3) Rempangan Sub-watershed, such as planting cover crops, coffee, and lamtoro terracing, (sengon, coffee, and terrace), reforestation with matoah, sengon, durian, avocado, petai, guava, (4) Rembangan Sub-watershed, such as grass strips, cover crops, (lamtoro, coffee, and terrace). The results of the second purpose are to identify roles, relationships, influence, and strength of stakeholders in the implementation of conservation governance using The Four Rs analysis and stakeholder strength analysis. The position and function of each stakeholder managing the upstream Bedadung Watershed, namely (1) LMDH and KTH as (Subject), (2) Branch of the Jember Regional Forestry Service, Perum Perhutani, and BPDAS Brantas Sampean as (Key Player), (3) Dinas Environment of Jember Regency, Bappeda Jember, Department of Public Works Bina Marga of Jember Regency, and Department of Agriculture of Jember as (Context Setters), (4) Brantas Sampean Watershed Forum as (Crowd).